2017
DOI: 10.1007/s40089-017-0206-2
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and photoluminescence of self-assembled CaWO4:Sm3+ microspheres: effect of pH and surfactant concentration

Abstract: Self-assembled CaWO 4 :Sm 3? microspheres were prepared via surfactant (sodium dodecyl sulfate) mediated hydrothermal method. The effect of pH and the concentration of surfactant on the morphology and photoluminescence of the synthesized phosphors have been studied. Samples were characterized by X-ray diffractometry (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and photoluminescence spectroscopy. The microspheres were found to have an average size of 1-2 lm. They were mesopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…This could suggest that Li + occupies the interstitial sites rather than the Y 3+ lattice sites similar to that. in YPO 4 :Eu 3+ as reported by Parchur et al 24,26 In Figure 1c, the variation of the fwhm and unit cell volumes are presented. The fwhm values are decreased with increasing Li + ion codoping.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…This could suggest that Li + occupies the interstitial sites rather than the Y 3+ lattice sites similar to that. in YPO 4 :Eu 3+ as reported by Parchur et al 24,26 In Figure 1c, the variation of the fwhm and unit cell volumes are presented. The fwhm values are decreased with increasing Li + ion codoping.…”
Section: Resultssupporting
confidence: 58%
“…1719 There are also reports on methods to enhance the luminescence emission such as codoping with certain metal (mono-, di- or tri-valent) ions in appropriate stoichiometry, tuning of synthetic parameters and morphological variations. 2024 The enhancement is effective when the codopant acts as a sensitizer or improves the crystallinity of the materials. The codoping of Li + in the YPO 4 :Dy 3+ system has improved the crystallinity and emissions of Dy 3+ including its near infrared band at 872 nm.…”
Section: Introductionmentioning
confidence: 99%
“…CaWO 4 nanocrystals are interesting and promising materials due to their excellent physical, chemical, and optical properties, such as intense photoluminescent emission at 420 nm. 1 Moreover, they are not toxic, when obtained by conventional methods of synthesis, and have a lower cost preparation, when compared with other semiconductors. Thus, the CaWO 4 material can be considered an important candidate for drug delivery or light-emitting devices (LEDs).…”
Section: Introductionmentioning
confidence: 99%
“…Calcium tungstate (CaWO 4 ) is a well-known semiconductor and an important member of the class of scheelite minerals. CaWO 4 nanocrystals are interesting and promising materials due to their excellent physical, chemical, and optical properties, such as intense photoluminescent emission at 420 nm . Moreover, they are not toxic, when obtained by conventional methods of synthesis, and have a lower cost preparation, when compared with other semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, our group has developed a combined coprecipitation and molten-salt synthesis (MSS) procedure to synthesize A 2 B 2 O 7 NPs size-controllably. The pH value of the coprecipitation step is a very important factor that governs the physical and microstructural properties of the synthesized NPs. While our synthesis procedure has many advantages, such as simplicity, greenness, reliability, scalability, and generalizability, , to the best of our knowledge, no study has been reported on the systematical investigation of the influence of the pH value during the synthesis of these NPs on their structural characteristics, defect chemistry, and luminescence properties.…”
Section: Introductionmentioning
confidence: 99%